Schwerpunktverlagerung, Richtung ungewiss?: Der "US-Pivot to Asia" und seine unintendierten Konsequenzen - Friedrichs, Gordon; Harnisch, Sebastian (Asien, 2016)
The phrase "unintended consequences" is often used in the political (science) discourse, yet it still remains theoretically underspecified. We conceptualize unintended consequences in role theoretical terms in three steps, and then apply it to the United States' policy vis-à-vis the Asia-Pacific region under the Obama administration - the so-called "Pivot to Asia". First, we model unintended consequences as a gap between the initial role-taking of an actor and the deviant but commensurate counter-role taking of an Other. Second, we examine the Obama administration's initial role-taking in the diplomatic, security, and economic realms, under the assumption that domestic contestation in the US may lead to unclear signaling about the Pivot's intentions. Third, we investigate counter-role taking by Japan, the Philippines, and Indonesia in order to draw conclusions about their interpretation of US role-taking and its consequences for the region's social structure. Our analysis exposes differentiated patterns of unintended consequences due to deviant counter-role taking by these nations vis-à-vis the US, China, and other actors in the region along all three dimensions of the Pivot.
Keywords: Obama, Barack -- 1961-; USA; Asien; Japan; Philippinen; Indonesien; Ostasien; Südostasien